2006
DOI: 10.7249/tr324
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Employment Conditions of Military Spouses

Abstract: The RAND Corporation is a nonprofit research organization providing objective analysis and effective solutions that address the challenges facing the public and private sectors around the world. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors.R ® is a registered trademark. © Copyright 2006 RAND CorporationAll rights reserved. No part of this book may be reproduced in any form by any electronic or mechanical means (including photocopying, recording, or informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…One of the many aspects of military family quality of life that DoD seeks to monitor and improve is the degree of employment opportunity available to spouses of military members (whom we refer to as military spouses). In advising DoD on how best to measure underemployment among military spouses, we argued in previous work (Lim and Golinelli, 2006) that the Labor Utilization Framework (LUF) is superior to traditional Bureau of Labor Statistics (BLS) measures of underemployment, such as the unemployment rate. In that work, we also proposed a set of additional survey questions that would provide enough information to construct the LUF measures of underemployment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the many aspects of military family quality of life that DoD seeks to monitor and improve is the degree of employment opportunity available to spouses of military members (whom we refer to as military spouses). In advising DoD on how best to measure underemployment among military spouses, we argued in previous work (Lim and Golinelli, 2006) that the Labor Utilization Framework (LUF) is superior to traditional Bureau of Labor Statistics (BLS) measures of underemployment, such as the unemployment rate. In that work, we also proposed a set of additional survey questions that would provide enough information to construct the LUF measures of underemployment.…”
Section: Discussionmentioning
confidence: 99%
“…To fully support military wives' efforts to gain adequate employment and to evaluate the effectiveness of its policies, DoD needs to measure military wives' labor market conditions and monitor the changes. To assist DoD with this effort, RAND published a report (Lim and Golinelli, 2006) that reviewed different measures of employment conditions. The authors identified the employment measures set forth in the Labor Utilization Framework (LUF) (see Hauser, 1974) as the most suitable for capturing military spouses' labor market position and behavior.…”
Section: Rand's Analysis Of Military Wives' Underemploymentmentioning
confidence: 99%
See 3 more Smart Citations